Improving Science Attitude and Character of High School Students Using the INSETS Learning Model Based on Local Wisdom Sopi of East Nusa Tenggara - Oetpah, Fincensius; Rahayu, Yuni Sri; Erman, Erman (International Journal of Current Educational Research, 2024)
Objective: This study examines the success of the INSETS model learning tool based on the local wisdom of Sopi culture of the Dawan tribe of East Nusa Tenggara to improve the science attitude skills and character of high school students. Method: This study applies the Instructional Design Model (IDM). Data were obtained from two observers who provided an assessment of the science attitude and character behavior of students shown by students during teaching and learning activities. Results: The results showed that the INSETS learning model based on the local wisdom of Sopi culture of the Dawan tribe of East Nusa Tenggara was effective in improving the science attitude skills and character of students, as evidenced by the results of the assessment of science attitudes and character of students during learning took place in the good to very good category. Novelty: Students' science attitude skills and character can be trained by integrating the INSETS learning model based on the local wisdom of Sopi culture of the Dawan tribe of East Nusa Tenggara to equip students in 21st Century education.